Experimental and Numerical Modeling Studies for Interpreting and Estimating the p–δ Behavior of Single Model Piles in Unsaturated Sands - Sheikhtaheri, Mohamadjavad (Université d'Ottawa / University of Ottawa, 2014)
The design of pile foundations in conventional geotechnical engineering practice is based on the soil mechanics principles for saturated soils. These approaches are also extended to pile foundations that are placed totally or partially above the ground water table (i.e., vadose zone), where the soil is typically in a state of unsaturated condition. Such approaches lead to unrealistic estimations of the load carrying capacity and the settlement behavior of pile foundations. Some studies were undertaken in recent years to understand the influence of the matric suction towards the bearing capacity of model pile foundations placed in unsaturated fine-grained and coarse-grained soils. The conventional   and methods were modified to interpret the contribution of shaft carrying capacity of single piles in fine-grained soils (e.g., Vanapalli and Taylan 2011, Vanapalli and Taylan 2012). Also, the conventional method has been used to understand the contribution of matric suction towards the shaft resistance in unsaturated sands (Vanapalli et al. 2010). One of the key objectives of the present research study is directed to determine the contribution of matric suction towards the bearing capacity and settlement behavior of model single pile foundations in unsaturated sands. A series of single model pile load tests were performed in a laboratory environment to study the contribution of the matric suction towards the total, shaft, and base bearing capacity of the model piles with three different diameters (i.e., 38.30, 31.75, and 19.25 mm) in two unsaturated sands (i.e., a clean commercial sand and a super fine sand). Hanging column method (i.e., plexi glass water container) was used to control the matric suction values in the compacted sands in the test tank by varying the water table. The results of the testing programs indicate the significant contribution of the matric suction towards the bearing capacity of single model piles (i.e., 2 to 2.5 times of base bearing capacity and 5 times of shaft bearing capacity under unsaturated conditions in comparison with saturated condition). The test results were interpreted successfully by modifying the conventional methods for estimating the pile shaft bearing capacity (i.e., β method) and base bearing capacity (i.e., Terzaghi 1943, Hansen 1970 and Janbu 1976). In addition, semi-empirical methods were proposed for predicting the bearing capacity of single model piles using the effective shear strength parameters (i.e., c' and ϕ') and the soil-water characteristic curve (SWCC). There is a good agreement between the measured and the predicted bearing capacity of single model piles using the semi-empirical models proposed in this study. In addition, numerical investigations were undertaken using the commercial finite element analysis program SIGMA/W (Geostudio 2007) to simulate the load-displacement (i.e., p-δ) behavior of the single model piles for the two sands (i.e., clean commercial sand and super fine sand) under saturated and unsaturated conditions. An elastic-perfectly plastic Mohr-Coulomb model that takes into account the influence of the matric suction was used to simulate the load-displacement (i.e., p-δ) behavior. The numerical approach proposed in this thesis is simple and only requires the information of the effective shear strength parameters (i.e., c' and ϕ'), the elastic modulus (i.e., Esat) under saturated conditions, the soil-water characteristic curve (SWCC), and the distribution of the matric suction with respect to depth. The approaches proposed in this thesis can be extended to determine the in-situ load carrying capacity of single piles and also simulate the load-displacement (i.e., p-δ) behavior. The studies presented in this thesis are promising and encouraging to study their validity in-situ conditions. Such studies will be valuable to implement the mechanics of unsaturated soils into geotechnical engineering practice.
Keywords: Single model pile; Unsaturated soils; p-δ behavior; Bearing capacity